TRANSFER IPTEK KELOMPOK MASYARAKAT HILIR (DOWNSTREAM) DI KELURAHAN KOMO LUAR MANADO - Pelle, Wilmy E; Wantasen, Adnan Sj (JURNAL PERIKANAN DAN KELAUTAN TROPIS, 2010)
The district of Komo Luar is one of the downstream areas of River Tondano. Based on some researches, performance of physic-chemical parameters show under of Indonesian Water Quality Guidelines e.g. dissolved oxygen, nitrate, phosphate, and e. colii. Knowledge and Technology Transferring has chosen in order to implement the soft approaches. Some programme has been done for example, training related to water quality and awareness campaign. We expected this programme could be modify the way of thinking of people around the river.